The effects of hypophysial portal plasma on the content of immunoreactive growth hormone in the anterior pituitary - Buse, M. G. (1970)
1. Blood plasma obtained from the hypophysial portal vessels of rats has been tested in assay animals for effects on the content of growth hormone in the anterior pituitary. 2. Growth hormone was estimated by radioimmuno-assay at 15 min, 30 min, 1 hr and 2 hr after intracarotid or intravenous infusion of portal plasma. There was a significant increase in growth hormone content at 15 min after infusion, but not at 30 min, 1 hr and 2 hr. 3. Insulin, cold stress, haemorrhage and treatment with growth hormone had no effect on growth hormone content of the pituitary under the conditions of application of these stimuli. 4. Growth hormone was measured in plasma obtained from the pituitary of control and insulin-treated animals. In control animals the amount of growth hormone in this plasma was higher than in base line samples and in the insulin-treated animals it was lower than in base line samples. A calculation based on the growth hormone content of blood obtained directly from the pituitary indicates a daily rate of synthesis and release of about 10 μg. 5. The hypothesis that portal plasma stimulated the synthesis of immuno-assayable growth hormone by the anterior pituitary is considered. 6. Discrepancies between our results using immuno-assay and those of others using bio-assay are discussed.